Sex estimations based on skeletal morphology - Strzałko, Jan; Henneberg, Maciej (Anthropological Review, 1975)
The authors have reviewed systematically the methods used for sexing the skeletal material on skull, pelvic bones, long bones and other parts of the skeleton. They have also described concisely the complex method used by Gy. Acsádi and J. Nemeskéri for estimation of the degree of sexualization in skeletal material.